Vitamin D boosts immune response of macrophages through a regulatory network of microRNAs and mRNAs (2022)
ABSTRACT: Vitamin D is associated with the stimulation of innate immunity, inflammation, and host defense against pathogens. Macrophages express receptors of Vitamin D, regulating the transcription of genes related to immune processes. However, the transcriptional and post-transcriptional strategies controlling gene expression in differentiated macrophages, and how they are influenced by Vitamin D are not well understood. We studied whether Vitamin D enhances immune response by regulating the expression of microRNAs and mRNAs. Analysis of the transcriptome showed differences in expression of 199 genes, of which 68% were up-regulated, revealing the cell state of monocyte-derived macrophages differentiated with Vitamin D (D3-MDMs) as compared to monocyte-derived macrophages (MDMs). The differentially expressed genes appear to be associated with pathophysiological processes, including inflammatory responses, and cellular stress. Transcriptional motifs in promoter regions of up- or down-regulated genes showed enrichment of VDR motifs, suggesting possible roles of transcriptional activator or repressor in gene expression. Further, the microRNA-Seq analysis indicated that there were 17 differentially expressed miRNAs, of which, seven were up-regulated and 10 down-regulated, suggesting that Vitamin D plays a critical role in the regulation of miRNA expression during macrophages differentiation. The miR-6501-3p, miR-1273h-5p, miR-665, miR-1972, miR-1183, miR-619-5p were down-regulated in D3-MDMs compared to MDMs. The integrative analysis of miRNA and mRNA expression profiles predicts that miR-1972, miR-1273h-5p, and miR-665 regulate genes PDCD1LG2, IL-1B, and CD274, which are related to the inflammatory response. Results suggest an essential role of Vitamin D in macrophage differentiation that modulates host response against pathogens, inflammation, and cellular stress.